IMPLEMENTASI BRANDING “PONDOK ASYIK” DI PONDOK SHIROTHUL FUQOHA’ ANAK DAN DAMPAK TERHADAP KARAKTER SANTRI - Muhammad Umar Faruq; Muhammad Husni (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2025)
The phenomenon occurring in society today shows a significant decline in the character of the younger generation. Gradually, young people are experiencing character degradation, causing parents to become increasingly concerned about this situation. This means that the younger generation must be guided and educated so they can grow into a resilient and strong generation. Islamic boarding schools (Pondok Pesantren) emerge within society as institutions that help address and anticipate these issues. This research is a qualitative study. The subjects of the research consist of 140 participants, including the caregivers of Pondok Pesantren Shirothul Fuqoha’ Anak, the head of the pesantren, administrators, and young students. The study was conducted from October 13–19, 2024 at Pondok Pesantren Shirothul Fuqoha’ Anak, Gondanglegi, Malang. Data collection techniques used were observation and interviews. Observation was aimed at exploring the “PONDOK ASYIK” branding and its positive impacts. The researcher gathered data through interviews with the children’s caregiver, K.H. Shofiyulloh, M.Pd., the head of Pondok Shirothul Fuqoha’ Anak, Ustadz Mohammad Sofi, M.H., nine pesantren administrators, and the head of RT 03 RW 02. Based on the results of this study, it can be concluded that the “PONDOK ASYIK” branding was implemented under the direction of the pesantren caregiver. This branding aims to increase the attractiveness of the institution so that parents will be encouraged to enroll their children. The term “Pondok Asyik” refers to a trustworthy institution that prioritizes politeness and good manners. It also provides assurance to the community that students are educated to be innovative and creative.